Poverty Stoplight - and povertystoplight.org (2018)
What is the Poverty Stoplight? The Stoplight is a tool that seeks to activate the potential of families and communities to lift themselves out of poverty. Using a technology platform, it offers a self-assessment survey and intervention model that enables people to develop practical solutions to overcome their specific needs. We work with organizations from different sectors around the world and bring together a network of powerful actors with one clear mission: eliminate poverty worldwide. The Stoplight Community is comprised of government agencies, private companies, small and medium-sized enterprises, non-profits, cooperatives, microfinance organizations, academic institutions, and sports clubs, among others.